Hubungan Kualitas Pelayanan Rawat Inap Dengan Indeks Kepuasan Masyarakat Puskesmas Wonosari - Mulyati, Lilik (Jurnal Keperawatan Profesional, 2020)
Community satisfaction measurements are intended to determine the level of community satisfaction with the services provided and provide an opportunity for the community to assess the services that have been received.The design of this study is quantitative with a Cross-Sectional approach. The study was conducted by involving 59 respondents taken by accidental sampling. The study was conducted in April until May 2019 at Wonosari Health Center, Bondowoso Regency. The measuring instrument used was a questionnaire, then bivariate analysis was performed with Spearman Rank Analysis, with a significance of p = 0.05. The results of the Spearman Rank statistical test with significance levels p <0.05. Obtained p-value 0,000 which means There is a Relationship between the Quality of Inpatient Services and the Wonosari Community Health Center Community Satisfaction Index with a correlation coefficient of 0.714. The quality of inpatient care results in an index of community satisfaction when receiving health services provided. The quality of this service can ultimately provide several benefits, including the establishment of harmonious relationships between service providers and customers, providing a good basis for creating customer loyalty and building a favorable recommendation for these service providers.